Strategy And Tactics Of Scientific Dispute - Turabova Sevara Kattaqulovna (Periodica Journal, 2023)
The article analyzes the need to implement a special strategy and tactics of the speech concept to achieve the goal in a scientific dispute, as well as the requirement for a clear planning of step-bystep actions to achieve the goal set in a scientific discussion. The rationale for the use of certain strategies and tactics depending on the type of dispute is described. Also, on the basis of scientific sources, the classification features of the strategy and tactics of conducting discussions, practical discussions, in particular aspects of setting and solving problems, were analyzed.
Keywords: strategy; dispute; method